Modification of bladder thermodynamics in stress urinary incontinence patients submitted to trans-obturator tape: A retrospective study based on urodynamic assessment - Lau, Hui-Hsuan; Lai, Cheng-Yuan; Peng, Hsien-Yu; Hsieh, Ming-Chun; Su, Tsung-Hsien; Lee, Jie-Jen; Lin, Tzer-Bin (Frontiers in Bioengineering and Biotechnology, 2022)
ABSTRACT Importance: If the trans-obturator tape (TOT)-enhanced urethral resistance could impact voiding function needs to be clarified. Objective: Though TOT is well-recognized to enhance urethral resistance to restore continence in stress urinary incontinence (SUI) patients, if bladder’s voiding functions adapt to the TOT-enhanced resistance is not adequately investigated. This study aimed to investigate whether TOT impacts bladder’s thermodynamic efficacy during voiding phase. Design: A retrospective analysis of urodynamics performed before and after TOT was assessed. Setting: A tertiary referral hospital in Taiwan. Participants: 26 female SUI patients who received urodynamic investigations before and after TOT Main Outcomes and Measures: The area enclosed by the pressure-volume loop (Apv), which represents the work performed by the bladder in a voiding, in a pressure-volume analysis (PVA) established by plotting the detrusor pressure versus intra-vesical volume was retrospectively analyzed. Paired Student’s t-tests were used to assess the difference of values before and after operation. A significance in difference was set at p<0.05. Results: TOT increased Apv in 20 of 26 (77%) patients and significantly increased the mean Apv compared to the pre-operative control (2.17±0.18 and 1.51±0.13 X103 cmH2O-ml, respectively p<0.01). TOT also increased the mean urethral resistance (1.03±0.30 vs. 0.29±0.05 cmH2O-sec/ml, p<0.01) and mean voiding pressure (25.87±1.72 and 19.30±1.98 cmH2O p<0.01) but did not affect voided volume and voiding time. Moreover, the TOT-induced Apv increment showed moderate correlations with the changes in urethral resistance and voiding pressure (both r>0.5) but no correlation with the changes in voided volume or voiding time. Remarkably, the TOT-induced urethral resistance increment showed a strong correlation with the change in voiding pressure (r>0.7). Conclusions and Relevance: The bladder enhances thermodynamic efficacy adapting voiding mechanism to the increased urethral resistance caused by TOT. Further studies with higher case series and longer follow-up should assess whether this effect could be maintained over time or expire in a functional detrusor decompensation, in order to define diagnostic criteria that allow therapeutic interventions aimed at preventing it during the follow-up. Clinical Trial Registration: ClinicalTrials.gov (NCT05255289).